Analysis of the acoustic properties and vertical distribution patterns of mesoand bathypelagic fish, and their contribution to the biological pump - Sarmiento Lezcano, Airam Nauzet (2023)
Programa de Doctorado en Oceanografía y Cambio Global por la Universidad de Las Palmas de Gran Canaria This thesis presents novel results on carbon remineralization by the most abundant nonmigrator meso- and bathypelagic fishes on the earth (Cyclothone spp.), on the seasonality of migrant micronekton active flux, on the swimbladder properties of six Cyclothone species inhabiting the meso- and bathypelagic layers in the North Atlantic Ocean and Mediterranean Sea, and on the use of acoustic scattering as a proxy for mesopelagic abundance/biomass. Micronekton is mainly composed of cephalopods, crustaceans and fishes. These organisms represent an important resource for higher trophic levels and are a key component of the biological carbon pump, contributing through diel vertical migrations (DVM) in the case of migrants, and through remineralization in the case of non-migrants. The vertical migrators feed at shallow ocean layers and release carbon at depth through respiration, defecation, excretion, moulting, and mortality. Recent studies suggest that migrant micronekton transport similar amounts of carbon to migrant zooplankton. However, there is scarce information about biomass and carbon flux by non-migratory species in the mesopelagic and bathypelagic zones, and the seasonality of migrant micronekton active flux. In order to understand the contribution of carbon flux by non-migratory bristlemouth fishes (Cyclothone spp.) and partial migrator (Argyropelecus hemigymnus) we provide the first account of remineralisation by this community in the meso and bathypelagic zones from the oceanic upwelling off Northwest Africa to the south of Iceland (North Atlantic Ocean). We estimated that total carbon remineralisation in the meso and bathypelagic zone by these organisms was about 1%. We also studied the seasonal variability (June and October) of migrant biomass and respiratory carbon flux of numerically dominant pelagic crustaceans and mesopelagic fishes in the Gulf of California, a semi-enclosed sea (North East ...